Comparative analysis of matches of Russian teams in freestyle and female wrestling - Latishev, S.; Korobeynikov, G.; Latishev, N. V.; Curby, D. G.; Korobeynikova, L. G.; Tropin, Y. (International Journal of Wrestling Science, 2018)
The results of the performances of the Russian National Teams in Freestyle and Women`s wrestling at the European Championships, World Championships and Olympics Games for the period from 1993 to 2016. Freestyle Team performs stably and successfully at all competitions, and the percentage of medalists is within 60 - 77.34% of the number of participants, more than half of the medals - gold. The results of the performance of the Women`s Team are comparable to the results of the Freestyle Team only at European Championships, and at the World Championships and Olympics Games, the women`s performance is much weaker. Kew words: Freestyle and Women`s wrestling, competitions, Championships, Olympics Games.